(3GdeNJGQ ef QSGFd CHj ESMGb EHQGgjes ((3GHf GdNGRf GdcGJH s)
(3ChdgG (B:s
(3fSNI cJGH CfTCg YfO aJM HZOGO hGfgRe GdCJQGc YfgG ai LeGOi GdChdi SfI (B364 (3CeG HYO aEf ddg bVGjG fGaPI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B21 - (3U (B523 s
(3eUOQ GbJfGA GdCUd (B:s
(3QFjS GdcJGH (B(317) s
Keywords: (3GdCOHs